Radiographic Evaluation of Elbow Fractures - Alidina, Sameer; Alidina, Jasim; Souza, Felipe; Kalandiak, Steven; Subhawong, Ty K. (Seminars in Musculoskeletal Radiology, 2021)
Fractures and dislocations of the elbow are a common cause of emergency department visits each year. Radiography remains the bedrock of an initial injury assessment, and recognition of distinctive injury patterns based on fracture location, morphology, and severity, guides optimal clinical decision-making. This article reviews basic elbow anatomy, frequently seen fractures and injury patterns, and highlights how these findings influence surgical planning and patient management.
Keywords: elbow; fracture; radiograph; trauma